Partnering for development donor report 2017. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication is intended for current and prospective official and other concessional development financing partners of the Asian Development Bank (ADB). It focuses on the importance of partnerships, results achieved, and ADBs reporting of results. This report features stories of successes illustrating the effectiveness of partnerships and the improvements they can make in the lives of the poor in vulnerable countries that need support. ADB partners benefit from the wide range of financing options presented here as they seek to begin or expand their commitment to developing Asia and the Pacific and to support ADBs strategic priorities confirmed during the midterm review of its long term strategic framework, Strategy 2020.
Keywords: Public-private sector cooperation -- Asia -- Finance; Electronic books